Association Between Sleep Apnea and Valvular Heart Diseases - Pelaia, Corrado; Armentaro, Giuseppe; Miceli, Sofia; Perticone, Maria; Toscani, Alfredo Francesco; Condoleo, Valentino; Spinali, Martina; Cassano, Velia; Maio, Raffaele; Caroleo, Benedetto; Lombardo, Nicola; Arturi, Franco; et al. (Frontiers in Medicine, 2021)
Background. Although sleep respiratory disorders are known as a relevant source of cardiovascular risk, there is a substantial lack of trials aimed to evaluate the eventual occurrence of associations between sleep apnea (SA) and valvular heart diseases (VHD). Methods. We recruited 411 patients referring to our sleep disorder unit, among which 371 had SA. 93 subjects with SA also suffered from VHD. Physical examination, echocardiography, nocturnal cardio-respiratory monitoring, and laboratory tests were performed in each patient. Patient subgroups were comparatively evaluated through cross-sectional analysis. Results. A statistically significant increase in the prevalence of VHD was detected in relation to high apnea hypopnea index (AHI) values (p = 0.011). Obstructive sleep apnea occurrence was higher in SA patients without VHD (p <0.0001). Conversely, central and mixed sleep apneas were more frequent among SA patients with VHD (p = 0.0003 and p = 0.002, respectively). We observed a direct correlation between AHI and BMI values (p <0.0001), as well as between AHI and serum uric acid levels (p <0.0001), high sensitivity C-reactive protein (p <0.0001), and indexed left ventricular end-diastolic volume (p <0.015), respectively. BMI and VHD resulted to be the main predictors of AHI values (p <0.0001). Conclusions. Our study suggests that a significant association can occur between SA and VHD. It is clinically relevant that when compared to SA patients without VHD, higher frequencies of central and mixed apneas were found in subjects with SA and VHD. Moreover, after elevated BMI, VHD represented the second predictor of AHI values.